Aktivitas Antidotum Air Kelapa Hijau (Cocos nucifera L.) terhadap Keracunan Sianida pada Mencit (Mus musculus L.) (Journal of Tropical Pharmacy and Chemistry, 2016)
Cyanide is a toxic compound that can interfere with health and reduce the nutrients bioavailability in the body. These toxins inhibit the body cells to get oxygen so that the most affected are the heart and brain. The aim of this study was to know the effect of green coconut water (Cocos nucifera L.) as an antidote to cyanide poisoning in mice (Mus musculus L.). The method was in vivo antidote activity using potassium cyanide-induced toxic mice. The mice were divided into 3 groups, i.e. negative control, positive control and test group with green coconut water giving 100% concentration. Each group consisted of 5 mice. Observations of toxic symptoms after the induction of potassium cyanide performed in initial times and and the results are analyzed visually by comparing graphs based on each group of tests during 24 hours of observation. The results showed that the green coconut water with 100% concentration that given in mice showed the influence of the reduction in toxic symptoms such as abnormal posture.  Recovery of toxic effect in the test group by giving green coconut water was no better than the positive control group by giving sodium nitrite and sodium thiosulfate.